Direito penal e direitos sociais: função promocional do direito penal? - Celestino, Bruno de Omena (2020)
This work aims to investigate criminal law’s promotional function, understood as crim-inal law’s use to achieve social rights and, consequently, social justice. On this doc-trine’s dogmatic basis lies the defense of the constitutional compatibility of criminal law’s use to promote social justice due to the modern Social and Democratic States of Law, where criminal law should be used to meet social rights’s achievement. However, the work is guided by the hypothesis that the this new concept of acting in criminal law’s adoption is not constitutionally adequate, being one of the roots of contemporary criminal protection’s problems, whether in terms of dogmatic or practical. This work’s objective is to investigate the premises that support criminal law’s promotional concep-tion, and its importance witch lies in fact that the topic does not receive much attention from the doctrine, although its methods are spread throughout the criminal legal sys-tem. The method for the work was to review the legal literature, focusing on national and foreign production. The research results obtained with the research were arranged in four chapters, investigating in sequence the most relevant topics. In the first chapter, the basic characteristics of social rights were highlighted as fundamental rights and how they demand promotional action from the State, exposing the doctrinal current that points to the supposed promotional function of criminal law. In the second chapter, historical and legal evolution’s investigation was promoted in order to establish the premises of the modern Social and Democratic State and Law, concluding that the current model is one that also rescues liberal values and does not require the perfor-mance of law in a promotional way. In the third chapter, it was exposed that the con-temporary legitimacy of criminal law is in its limiting and minimal function of the inter-vention of criminal law, in the logical-rational structure of criminal tutelage and in the adoption of humanistic values, recognized by most contemporary Western democratic constitutions, so the promotional function is not required to criminal law. In the last chapter, the hypothesis that criminal law has no promotional function was confirmed, because it does not serve to materialize social rights, either because it is incompatible with the constitutional foundation of the minimum criminal intervention, or because there is no evidence of any relevant role. played by criminal law in the promotion of social justice, while still being dissociated from the constitutional foundations of the penalty. Finally, conclusions were provided in order to respond to the problems that guided the present investigation, distinguishing between the illegitimate promotional function of criminal law and the constitutionally legitimate criminal protection of social rights